Does the region make a difference? : Social inequality in transitions to adulthood across cohorts in West Germany - Weßling, Katarina [Verfasser] (My University, 2023)
“Since the availability of study opportunities is unequal across regions, entering the phase of post-secondary education is often accompanied by leaving (the parental) home. In these life-course transitions, social background plays a crucial role in the form of resources, e.g., to afford living independently while studying. We use a unique set of geospatial data by aggregating information on the municipality level flexibly within travel-time radii and link the data to the German National Educational Panel Study (NEPS) to examine whether socioeconomic and university infrastructure in the region can compensate for a lack of parental resources (i) in transitions to university and (ii) in the likelihood of staying in or leaving the home region to study. We analyse this across cohorts between 1986 and 2015. We find that the region makes a difference: a wide availability of universities in the region offsets social inequality in the transition to university. Yet, the increasing availability of alternative educational routes over time via vocational training and universities of applied sciences causes this moderating influence to decrease across cohorts. Our findings call for gearing the attention of policymakers towards the varying relevance of regional conditions over time and across social groups for individuals’ life-course transitions.” (Autorenreferat; BIBB-Doku)
Keywords: G 1.3.2.2 Übergänge; S 1.4 Hochschulbildung; G 2.1.4 Regionalisierung; G 1.3.3.3 Mobilität; 370; 300; Bildungsentscheidung; Studium; Studienmöglichkeiten; Studienort; Studienortwahl; Region; Regionale Mobilität; Soziale Ungleichheit; Nationales Bildungspanel